2006
DOI: 10.1063/1.2168396
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of a Bohr atom model

Abstract: N. Bohr proposed in 1913 a model for atoms and molecules by synthesizing Planck's quantum hypothesis with classical mechanics. When the atom number Z is small, his model provides good accuracy for the ground state energy. When Z is large, his model is not as accurate but still provides a good trend agreeing with the experimental values of the ground state energy of atoms.The main objective of this paper is to provide a rigorous mathematical analysis for the Bohr atom model. We have established the following:(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…These calculations involve a simple minded minimization of classical functionals of the type considered by Bohr in 1913. Mathematical justification of such a procedure was found by Chen et al [13] The accuracy of results obtained with help of such classical calculations (employing however the B-S quantization rule !) compares well with incomparably more elaborate traditional quantum mechanical calculations.…”
Section: -Body Problem and The He Atom (Modern Perspective)mentioning
confidence: 99%
See 1 more Smart Citation
“…These calculations involve a simple minded minimization of classical functionals of the type considered by Bohr in 1913. Mathematical justification of such a procedure was found by Chen et al [13] The accuracy of results obtained with help of such classical calculations (employing however the B-S quantization rule !) compares well with incomparably more elaborate traditional quantum mechanical calculations.…”
Section: -Body Problem and The He Atom (Modern Perspective)mentioning
confidence: 99%
“…It follows that each permutation is a constant of motion. This happens even if the Hamiltonian is not constant 13 ." At this point it is important to recall the famous theorem by Caley [37] which states that "every finite group is isomorphic to some permutation group".…”
Section: General Commentsmentioning
confidence: 99%
“…In the Bohr's theory, the circular orbital length is equal to a integer times the wavelength of the electron, so we have, 2πr = n × h/mv. In several phenomena, the Bohr's model provides good accuracy [4,5,6]. But this model could not explain about the spin of the electron and the two-electron atoms such as the helium exactly.…”
mentioning
confidence: 99%
“…To put issues in perspective, Bohr's semiclassical theory of electronic structure may be applied to molecules and is known to deliver more accurate results than comes from many modern sophisticated DFT approaches. [308][309][310][311][312] The advantage of Bohr's approach is that it includes electron correlation simply and easily. Indeed, we have shown that a range of basic chemical phenomena like the nature of the valence states of transition-metal compounds, f-block chemistry, the basic description of NMR spectroscopy, relativistic effects in chemistry, etc., can be simply described at this level, providing an easy way to explain chemistry to freshman students.…”
Section: Strong But Highly Distributed Electron Correlation: the Van mentioning
confidence: 99%